2017
DOI: 10.3390/healthcare5010007
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Demographic Determinants of Diet Quality in Australian Adults Using the Validated Healthy Eating Index for Australian Adults (HEIFA-2013)

Abstract: Diet quality indices have been shown to predict cardiovascular disease, cancer, Type 2 Diabetes, obesity and all-cause mortality. This study aimed to determine the socio-demographics of Australian adults with poor diet quality. Diet quality was assessed for participants of the 2011–2012 National Nutrition and Physical Activity Survey aged 18 years or above (n = 9435), with the validated 11-component Healthy Eating Index for Australians (HEIFA-2013), based on the 2013 Australian Dietary Guidelines. Differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
58
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 53 publications
14
58
1
Order By: Relevance
“…Accurate assessment of dietary intake is essential to substantiate the link with academic achievement (7,8) ; for example, using validated dietary assessment tools and, ideally, a broad or holistic assessment of diet that goes beyond individual food groups or meal patterns. Furthermore, key factors that are known to influence diet or academic achievement need to be accounted for to more accurately assess this relationship, such as socio-economic status and gender (9,10) . In addition, five of the seven studies included in the review were conducted in America (5) , highlighting that there is no great diversity in the samples studied so far.…”
Section: Introductionmentioning
confidence: 99%
“…Accurate assessment of dietary intake is essential to substantiate the link with academic achievement (7,8) ; for example, using validated dietary assessment tools and, ideally, a broad or holistic assessment of diet that goes beyond individual food groups or meal patterns. Furthermore, key factors that are known to influence diet or academic achievement need to be accounted for to more accurately assess this relationship, such as socio-economic status and gender (9,10) . In addition, five of the seven studies included in the review were conducted in America (5) , highlighting that there is no great diversity in the samples studied so far.…”
Section: Introductionmentioning
confidence: 99%
“…A very basic measure of healthy eating is used in this analysis. This measure has been used in other studies exploring eating behaviour in an Australian population (Cobb‐Clark et al ) However, using a more detailed measurement of eating, such as a 24 hour recall food diary or a healthy eating measure validated for an Australian population such as the Healthy Eating Index for Australian Adults (HEIFA‐2013) (Grech et al ), may be able to give a more detailed picture of how market activities impact on dieting resolve.…”
Section: Resultsmentioning
confidence: 99%
“…The results of numerous studies have shown that high GI and/or high GL diets may increase the risk of type 2 diabetes [24], cardiovascular disease [13,14,15], metabolic syndrome [25] and cancer [26,27] development. On the other hand, many authors have proved that higher diet quality was associated with higher socio-economic status, including such determinants as: income, working status, marital status, and level of education [28,29,30,31]. A previous study conducted in Poland also showed a relationship between gender, age and level of education, and the nutritional value of the diets [32].…”
Section: Discussionmentioning
confidence: 99%
“…Dietary glycaemic load is a value that strongly correlates with the energy and macronutrient intake and therefore many authors propose to adjust GL for total energy intake [26,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. However some authors discuss the results of their studies only with reference to the overall dietary glycaemic load [38,39].…”
Section: Discussionmentioning
confidence: 99%